Bioprocessing for value-added products from renewable resources new technologies and applications - Yang, Shang-Tian (Elsevier, 2007)
Bioprocessing for Value-Added Products from Renewable Resources provides a timely review of new and unconventional techniques to manufacture high-value products based on simple biological material. The current source for most chemicals and materials is petroleum. Anticipation of its limited future availability, along with record high prices has spurred interest in alternatives that will be both sustainable and cost-effective. In a very structured way this book begins by describing the modern technologies that form the basis for creating a bio-based industry. Next it lists the various organisms that are suitable for bioprocessing -from bacteria to algae- and it gives their unique characteristics. These first two parts set the stage for a variety of novel, experimental bioprocesses, such as the production of medicinal chemicals, the production of chiral compounds and the design of biofuel cells. Concludes with examples where biological, renewable resources become an important feedstock for large-scale industrial production. Bioprocessing for Value-Added Products from Renewable Resources provides a unique perspective of the industry and the field and serves as an important guide towards the future. The book is suitable for researchers, practitioners, students, and consultants in the bioprocess and biotechnology fields. Reviews the principles underpinning modern industrial biotechnology Provides a unique collection of novel bioprocesses for a sustainable future Gives examples of economical use of renewable resources as feedstocks Suitable for both non-experts and experts in the bioproduct industry.
Keywords: Biochemical engineering.; Biotechnological process control.; Renewable natural resources.; elektronické knihy; electronic books